PEMIKIRAN FILOSOFIS KEPEMIMPINAN PERGURUAN TINGGI KEAGAMAAN ISLAM BERBASIS BUDAYA PONDOK PESANTREN (Studi Pada Sekolah Tinggi Agama Islam Rasyidiyah Khalidiyah Amuntai Kalimantan Selatan) - Wahyudin; Muhammad Zakiyyul Fuad Rasyid (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Objective: The objective of this study is to identify and examine the philosophy of academic leadership at STAI Rasyidiyah Khalidiyah Amuntai, which is based on the cultural values of Islamic boarding schools. Methodology: This study employs a qualitative approach using a case study design. Sampling techniques utilised in the study included targeted sampling and snowball sampling. The research instruments used were observation, interviews, and document review. Data analysis was conducted using an inductive conceptualisation approach. Findings: The results of this study indicate that the leadership philosophy at STAI Rasyidiyah Khalidiyah Amuntai encompasses (1) the nature of the philosophy, which includes dedication, sincerity, blessings, and flexibility in facing challenges. (2) Sources of the philosophy, derived from social traditions, the culture of the surrounding community, the founders (muassis), leaders, teachers (mu'allim), key figures within the foundation, the vision and mission, and leadership figures. (3) Internalisation of the philosophy, the internalisation of the philosophy is an ongoing process, utilising various approaches to internalise the leadership philosophy, practices within the boarding school and campus, and platforms such as meetings and other ceremonial events also play a significant role. (4) Philosophical awareness: awareness and appreciation of the foundational (primordial) philosophy; this philosophy is actively applied in operations; and the boarding school culture forms an integral part of campus life, influencing philosophical awareness. (5) Development of philosophy, no development (the entire academic community has adhered to the institution’s philosophy from the outset); the existing social philosophy remains strong and forms the basis for all organisational decisions and actions, and existing leadership figures reinforce the values of the leadership philosophy. (6) Documentation of the philosophy: the leadership philosophy is not documented in writing and is not physically represented within the organisation’s facilities; furthermore, this philosophy has not been comprehensively studied in relation to various aspects of the organisation’s operations.